2019
DOI: 10.1093/jbcr/irz156
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Research Productivity of Burn Surgeons: Results from a Survey of American Burn Association Members

Abstract: While previous studies have examined factors that affect research productivity for surgeons in general, few studies address research productivity specifically of burn specialists. This study aimed to identify factors that promote and impede research participation and productivity of burn surgeons and help elucidate what changes can be made by departments/divisions to improve the research productivity. A 44-question anonymous research survey tool was administered to burn surgeons who are members of the American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Prior studies have further elaborated on these difficulties and issues that have arisen and affected the research productivity of surgeons throughout all fields. [4][5][6] One of the major factors of decreased surgeon research productivity is lack of support from their surgical department, which often presents itself as lack of protected research time, lack of department funding, and overall lack of support. Ko et al 2 reported that with healthcare system changes, more surgeons find the need to dedicate their time to administrative and clinical duties rather than research endeavors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have further elaborated on these difficulties and issues that have arisen and affected the research productivity of surgeons throughout all fields. [4][5][6] One of the major factors of decreased surgeon research productivity is lack of support from their surgical department, which often presents itself as lack of protected research time, lack of department funding, and overall lack of support. Ko et al 2 reported that with healthcare system changes, more surgeons find the need to dedicate their time to administrative and clinical duties rather than research endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overall survey content were derived from current evidence-based research. 4,5,8,9,14 Institutional resources and support were defined by the following parameters: statistical support, start-up funds, grant writing support, structured mentorship, research staff, laboratory space, equipment, financial support, and protected research time.…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The same study reports that mentorship, advanced degree, and membership in societies have a positive impact on research productivity. 11 Another study done on authorship in collaborative health research in Africa showed that affiliation with a top US university increased the likelihood of being a first and last author. 12 There has been little research within the surgical field on institutional affiliation and authorship trends.…”
Section: Introductionmentioning
confidence: 93%
“…19 In fact, the lack of protected time and institutional resources, including training in research design and conduct, has been identified as one of the greatest barriers to research involvement among physicians in various specialties. 9,21 Notably, however, a program's designation of a "research requirement" was not shown to have a significant impact on departmental productivity in the large neurosurgery resident cohort mentioned above. Authors of that study reasoned that research is engrained in the culture of many of the highly productive programs and does not require formal designation, while programs with an explicit requirement may be in the early stages of such a culture change.…”
mentioning
confidence: 99%